Koding Matematika Menggunakan Excel Pada Siswa SMPN 5 Indralaya Utara Di Desa Tanjung Baru Ogan Ilir: Enhancing Mathematical Literacy Through Excel-Based Computational Coding for Junior High School Students in Tanjung Baru Village, Ogan Ilir Regency - Hanum, Herlina; Kresnawati, Endang Sri; Yama Otantia P, Soya Febeauty; Setyawan, Dwi (Jurnal Hilirisasi IPTEKS, 2026)
Mathematical and language literacy are fundamental competencies that support students' learning across various disciplines. One effective approach to enhancing mathematical literacy is the use of mathematical coding through spreadsheet software such as Microsoft Excel. This community engagement program aimed to improve the mathematical literacy and Excel-based coding skills of students at Junior High School 5 North Indralaya, Ogan Ilir Regency, Indonesia. The program was implemented through training and mentoring sessions conducted in the school's computer laboratory, involving 32 students who shared 16 computers. Students learned to apply Excel formulas and functions to solve mathematical problems. The training consisted of three sessions, each lasting two instructional hours, covering basic arithmetic, plane and solid geometry, and introductory statistics. Although the participants had not formally studied statistics, they successfully used Excel formulas to calculate the mean, median, mode, maximum, and minimum values. Program effectiveness was evaluated using pre-test and post-test assessments. The results demonstrated significant improvements in both mathematical literacy and Excel-based coding skills. All students showed better mathematical performance, as indicated by the increased number of correct answers across all mathematical problems. Coding proficiency also improved substantially; while only two students correctly answered the Excel coding questions in the pre-test, all participants answered them correctly in the post-test. These findings indicate that Excel-based mathematical coding is an effective instructional approach for strengthening mathematical literacy, computational thinking, and digital skills among junior high school students.